Teaching Science Mapping Research on Integration of Augmented Reality Technology and Education for Sustainable Development: A Bibliometric Analysis - Azifa Feziyasti; Asrizal; Hazrati Ashel (Postgraduate, University of Mataram, 2025)
The integration of technology and sustainability education is essential to develop students’ 21st-century skills. AR and ESD offer innovative pathways to enhance science learning in addressing global challenges. However, the development of research combining AR and ESD in science education has not been comprehensively mapped. This study aims to analyze trends and directions of research on the integration of AR and ESD using bibliometric analysis. Data were collected from Scopus indexed articles published between 2015 and 2025 and analyzed using VOSviewer through performance analysis, co-authorship, keyword co-occurrence, and thematic mapping. The results show a steady increase in publications, with research clusters highlighting themes such as immersive learning, sustainability awareness, digital pedagogy, and interdisciplinary approaches. Visualization reveals AR as a powerful experiential tool for promoting ESD values in science classrooms. This study also identifies future opportunities, such as enhancing pedagogical frameworks, expanding real world applications of AR, and strengthening collaboration across education, technology, and environmental disciplines. The findings suggest that integrating AR and ESD can foster more interactive, meaningful, and sustainability-oriented science education. This study recommends further development of immersive AR based teaching strategies aligned with the goals of sustainable development.